2022
DOI: 10.3389/fmicb.2022.949002
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiota Determines the High-Altitude Adaptability of Tibetan Wild Asses (Equus kiang) in Qinghai-Tibet Plateau

Abstract: It was acknowledged long ago that microorganisms have played critical roles in animal evolution. Tibetan wild asses (TWA, Equus kiang) are the only wild perissodactyls on the Qinghai-Tibet Plateau (QTP) and the first national protected animals; however, knowledge about the relationships between their gut microbiota and the host's adaptability remains poorly understood. Herein, 16S rRNA and meta-genomic sequencing approaches were employed to investigate the gut microbiota–host associations in TWA and were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 75 publications
1
10
0
Order By: Relevance
“…Treponema 2 was found to be the main genus responsible for this difference (9.69% for R. brelichi vs. 1.22% for R. roxellana, P < 0.05). Treponema 2 has enzymes that mediate pyruvate oxidation and decarboxylation to enter the citrate cycle, promoting the biosynthesis of arginine and fatty acids ( 39 ). The proportion of Proteobacteria was significantly higher in R. roxellana , and the relative abundance of the genus Parasutterella was significantly higher than in R. bieti and R. brelichi ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Treponema 2 was found to be the main genus responsible for this difference (9.69% for R. brelichi vs. 1.22% for R. roxellana, P < 0.05). Treponema 2 has enzymes that mediate pyruvate oxidation and decarboxylation to enter the citrate cycle, promoting the biosynthesis of arginine and fatty acids ( 39 ). The proportion of Proteobacteria was significantly higher in R. roxellana , and the relative abundance of the genus Parasutterella was significantly higher than in R. bieti and R. brelichi ( P < 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Treponema was the main genus responsible for this difference (10.22% for R. brelichi vs. 1.30% for R. roxellana, P < 0.05). Treponema has enzymes that mediate pyruvate oxidation and decarboxylation to enter the citrate cycle, promoting the biosynthesis of arginine and fatty acids [ 36 ]. It has been suggested that low-abundance bacteria that are not normally part of the core community are drivers of changes in the composition of the host post-gut microbiota [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, due to data unavailability, the data on carbon metabolism for plateau pika were applied to Chinese zokor in this study. The digestive rate for wild yak is likely higher than that of domestic yak living in the same area (H. Liu et al, 2022; Y. Xu & Xu, 1998). The Tibetan wild ass is a monogastric herbivore, however, and its forage digestive rate is similar to domestic yak (H. Liu et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The digestive rate for wild yak is likely higher than that of domestic yak living in the same area (H. Liu et al, 2022; Y. Xu & Xu, 1998). The Tibetan wild ass is a monogastric herbivore, however, and its forage digestive rate is similar to domestic yak (H. Liu et al, 2022). Therefore, the carbon metabolism parameters for the ungulate species were inferred from livestock in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation